Current status of phylogenetic studies on ciliated protists (Alveolata, Protozoa, Ciliophora) by the OUC-group: advances, challenges and future perspectives - Feng Gao; Yang Bai; Yong Chi; Xiaochen Feng; Chunyu Lian; Borong Lu; Xiaotian Luo; Mingzhen Ma; Congcong Wang; Yurui Wang; Zhe Wang; Gongaote Zhang; et al. (Marine Life Science & Technology, 2025)
Ciliated protists (ciliates) represent a morphologically and genetically diverse group of single-celled eukaryotes, the phylogeny of which is critical for understanding eukaryotic evolution. Through international collaborations, the Laboratory of Protozoology at Ocean University of China (OUC-group) has conducted detailed research on ciliate phylogeny based on expanded taxonomic sampling, employing single gene as well as multi-gene markers, and phylogenomic datasets. We have systematically investigated > 1000 ciliate species spanning ~ 40 orders, sampled from diverse biotopes including marine environments in China seas and freshwater wetlands. This comprehensive sampling has generated three key datasets: (1) genomic DNA extracts from ~ 2600 strains, (2) ~ 2300 sequences of marker genes, and (3) single-cell genomic and/or transcriptomic datasets from ~ 120 species. Based on these datasets, the phylogenetic relationships covering all classes and most orders have been thoroughly reconstructed and investigated, resulting in the establishment of 93 new supraspecies taxa comprising two classes (Mesodiniea and Protocruziea), two subclasses (Protohypotrichia and Synhymenia), two orders (Wilbertomorphida and Lynnellida), 11 families, and 76 genera. Moreover, we have reconstructed a genome-scale tree of life for ciliates and provided an updated classification of the phylum Ciliophora. Furthermore, based on the robust phylogenetic tree of ciliates, we provide more reliable estimates for the origins and divergence times of the main ciliate groups. Future studies integrating advanced genomics, innovations in culturing and interdisciplinary applications will refine the ciliate tree of life, with broader impacts for our understanding of eukaryotic evolution and biodiversity.